2011
DOI: 10.1073/pnas.1015762108
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic ozonide drug candidate OZ439 offers new hope for a single-dose cure of uncomplicated malaria

Abstract: Ozonide OZ439 is a synthetic peroxide antimalarial drug candidate designed to provide a single-dose oral cure in humans. OZ439 has successfully completed Phase I clinical trials, where it was shown to be safe at doses up to 1,600 mg and is currently undergoing Phase IIa trials in malaria patients. Herein, we describe the discovery of OZ439 and the exceptional antimalarial and pharmacokinetic properties that led to its selection as a clinical drug development candidate. In vitro, OZ439 is fast-acting against al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
365
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(381 citation statements)
references
References 38 publications
11
365
0
4
Order By: Relevance
“…More impressively, ELQ-400 also effectively cleared asexual, blood-stage parasites with a single 1 mg/kg dose, making it the most active single-dose therapy to date, with a 20-fold to 100-fold increase in efficacy over other single-dose compounds in the developmental pipeline. [11][12][13] As with other single-dose antimalarials, we also found that ELQ-400 was capable of rapidly reducing blood-stage parasitemia in vivo. This finding was especially striking because cyt bc 1 inhibitors such as ELQ-400 have generally been classified as slow-onset antimalarials.…”
Section: Elq-400 Single-dose Antimalarial Therapysupporting
confidence: 71%
See 1 more Smart Citation
“…More impressively, ELQ-400 also effectively cleared asexual, blood-stage parasites with a single 1 mg/kg dose, making it the most active single-dose therapy to date, with a 20-fold to 100-fold increase in efficacy over other single-dose compounds in the developmental pipeline. [11][12][13] As with other single-dose antimalarials, we also found that ELQ-400 was capable of rapidly reducing blood-stage parasitemia in vivo. This finding was especially striking because cyt bc 1 inhibitors such as ELQ-400 have generally been classified as slow-onset antimalarials.…”
Section: Elq-400 Single-dose Antimalarial Therapysupporting
confidence: 71%
“…9,10 Several potential single-dose cure antimalarials are currently in the developmental pipeline. The ozonide OZ439, 11 the aminopyridine MMV390048, 12 and the spiroindolone NITD609 13 all effectively clear asexual, blood-stage parasites in mouse models of malaria with a single oral dose and also inhibit gametocyte development, which reduces the potential for malaria transmission. In contrast, several imidazolopiperazines, 14,15 8-aminoquinolines, 16 and antirespiratory compounds 17,18 have been identified as single-dose causal prophylactics, which inhibit the sporozoite and liverstage parasites that are responsible for the earliest stages of Plasmodium infection.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, we anticipate that use of endoperoxides with longer exposure in the bloodstream will prevent parasite escape via short-term growth arrest. In this regard synthetic endoperoxides with improved in vivo half-lives that are currently under development hold great promise (32,41,42). A better appreciation of the interaction of artemisinins and partner drugs with the hemoglobin degradation pathway may uncover additional strategies to protect the vital resource of endoperoxide antimalarials.…”
Section: Discussionmentioning
confidence: 99%
“…The spiroindolone compound NITD609, a potent inhibitor of P. falciparum selected in a phenotypic HTS of natural products, is also undergoing Phase I trials (Rottmann et al 2010). The ozonide OZ439, a synthetic peroxide antimalarial that is designed to provide a single oral dose to cure human malaria, is currently undergoing Phase II trials (Charman et al 2011).…”
Section: Drugs Available To Treat Other Human Diseases -mentioning
confidence: 99%